Computational Analysis and Optimization of Polymer-Based Ankle-Foot Orthoses - Rusul Salah Hadi; Hala Mahmood Kadhim (Advances in Polymer Technology)
In this study, three main materials, polypropylene (PP), carbon fiber-reinforced polymer (CFRP), and thermoplastic elastometers. This work aims to offer a computational evaluation of the mechanical and thermal performance of an ankle-foot orthosis (AFO). A thorough three-dimensional (3D) model of the AFO was built, and meshing with more than 5000 components was executed to guarantee that the simulation is correct under temperature and fatigue stress conditions. Whereas PP and TPEs have ultimate tensile strength (UTS) values of 32 and 20 MPa, respectively, CFRP boasts the highest mechanical strength with a UTS of 340 MPa and a modulus of elasticity of 25 GPa. With its greatest modulus of elasticity, CFRP shows the best mechanical strength among the materials. Although TPEs showed notable distortion, thermal simulations showed that CFRP kept dimensional stability under heat. CFRP improved fatigue life by more than 30%, compared to PP and TPEs. CFRP is thus the substance most suitable for usage under high degrees of stress over a long length of time. Under physiological stresses, the enhanced general structural stability and 27% reduction in peak stress from the optimal design are guaranteed. These results underline the need for choosing composite materials in terms of enhancing the performance of AFOs as well as their lifetime and heat resistance in orthopedic uses. This guarantees the orthosis keeps its structural integrity and fit throughout usage, therefore improving patient comfort and functional support.